Social Class and EFL Learning in Indonesia: Listening to Teachers’ Perception - Usep Sofyana; John Pahamzah (Journal of English Language Teaching and Cultural Studies, 2022)
The social class status strongly affects the experience of students in language learning.  The objective of this study is to explore the belief of teachers on social class and its influence on language learning in the EFL class. This study applied a hermeneutic phenomenological qualitative method. The sample of this study was English teachers in bilingual primary school in Serang, Banten. Six teachers were selected as a sample using the purposeful sampling technique. The findings show that teachers believed that social class differences affect the language learning in the EFL class. The higher class students tend to obtain the supportive learning environment than lower social class students. Another finding also revealed that teachers believed that students from higher class families have better language such in vocabularies and pronunciation. These findings provided additional support to the need of intensive support for students from lower class families to fill the gaps of the language learning that is caused by the social class difference.